Information Technology teaching the Methods for the Organism Recovery at Home Conditions - Fainzilberg, L.S.; Pomorska, D.V. (Управляющие системы и машины, 2018)
The information technology that provides learning the body recovery methods at home was developed. The technology is based on a mobile application running under Android operating system, which implements functions of a virtual instructor, with the help of a 3D model. To analyze the results, a computer system FASEGRAPH® was used which automatically determines ordinary and original parameters of a single channel electrocardiogram as well as a modern fitness sensor Xiomi My Band 2, which gives the opportunity to monitor sleep with the help of the built-in pulse meter.